THE INFLUENCE OF HUMAN RESOURCE COMPETENCIES, BUDGET PLANNING AND BUDGET IMPLEMENTATION ON BUDGET ABSORPTION OF REGIONAL APPARATUS ORGANIZATIONS (OPD) IN BATAM CITY GOVERNMENT - Anisa Sangadji; Sabri; Sumardin (CV. Radja Publika, 2026)
This study aims to determine and analyze the influence of Human Resource Competence, Budget Planning, and Budget Implementation on Budget Absorption of Regional Apparatus Organizations (OPD) in the Batam City Government. This study was conducted at OPDs of the Batam City Government with a total of 89 respondents. The variables used in this study consist of Human Resource Competence (X1), Budget Planning (X2), Budget Implementation (X3), and Budget Absorption (Y).The data analysis methods used were simple linear regression and multiple linear regression to determine the relationship and influence between the independent variables on the dependent variable. Hypothesis testing was conducted using the t-test (partial), F-test (simultaneous), and coefficient of determination (R²) test. Data processing was performed using SPSS statistical software.